Life cycle approach to sustainability assessment: A case study of remanufactured alternators - Erwin M. Schau; Marzia Traverso; Matthias Finkbeiner (Journal of Remanufacturing, 2012)
Sustainability is an international issue with increasing concern and becomes a crucial driver for the industry in international competition. Sustainability encompasses the three dimensions: environment, society and economy. This paper presents the results from a sustainability assessment of a product. To prevent burden shifting, the whole life cycle of the products is necessary to be taken into account. For the environmental dimension, life cycle assessment (LCA) has been practiced for nearly 40 years and is the only one standardised by the International Organization for Standardization (ISO) (14040 and 14044). Life cycle approaches for the social and economic dimensions are currently under development. Life cycle sustainability assessment (LCSA) is a complementary implementation of the three techniques: LCA (environmental), life cycle costing (LCC - economic) and social LCA (SLCA - social). This contribution applies the state-of-the-art LCSA on remanufacturing of alternators aiming at supporting managers and product developers in their decision-making to design product and plant. The alternator is the electricity generator in the automobile vehicle which produces the needed electricity. LCA and LCC are used to assess three different alternator design scenarios (namely conventional, lightweight and ultra-lightweight). The LCA and LCC results show that the conventional alternator is the most promising one. LCSA of three different locations (Germany, India and Sierra Leone) for setting the remanufacturing mini-factory, a worldwide applicable container, are investigated on all three different sustainability dimensions: LCA, LCC and SLCA. The location choice is determined by the SLCA and the design alternatives by the LCA and LCC. The case study results show that remanufacturing potentially causes about 12% of the emissions and costs compared to producing new parts. The conventional alternator with housing of iron cast performs better in LCA and LCC than the lightweight alternatives with aluminium housing. The optimal location of remanufacturing is dependent on where the used alternators are sourced and where the remanufactured alternators are going to be used. Important measures to improve the sustainability of the remanufacturing process in life cycle perspective are to confirm if the energy efficiency of the remanufactured part is better than the new part, as the use phase dominates from an environmental and economical point of view. The SLCA should be developed further, focusing on the suitable indicators and conducting further case studies including the whole life cycle.
Keywords: 650; life cycle sustainability assessment; life cycle assessment; life cycle costing; social LCA; remanufacturing; alternator; automotive parts; Germany; India; Sierra Leone; Produktlebenszyklus; Lebenszykluskosten; Produkt-Recycling; Ersatzteil; Automobilzulieferindustrie; Deutschland; Indien; Sierra Leone